Dosimetric optimization of a truncated conical-shaped transmission target for electronic brachytherapy X-ray source: A Monte Carlo study - Ahn, Woo Sang; Choi, Wonsik; Cho, Byungchul; Kwak, Jungwon; Ahn, Seung Do; Kim, Hyun Jin; Cho, Sung Oh; Park, Sung Ho; Shin, Seong Soo (Journal of the Korean Physical Society, 2017)
The purpose of this study is to determine the optimal target configurations to improve the uniformity of dose distribution for the electronic brachytherapy source. A truncated conical-shaped transmission type was designed. Monte Carlo simulation technique was used to investigate the target thickness, geometry of electron beam, and target angle of a truncated conical-shaped target for the electronic brachytherapy X-ray source. Dosimetric parameters recommended by TG-43U1 protocol were used to determine the optimal target design of electronic brachytherapy source. The target thicknesses for maximizing the transmitted X-ray intensity were approximately 1.2 to 1.5 μ m for 0° and 90°. In a range of optimal thickness, transmitted X-ray intensity at 90° was approximately 92% of maximum photon intensity. The effects of electron beam shapes on 2D anisotropy functions were investigated at radial distances of 0.5, 1.0, 2.0, 3.0, and 5.0 cm. Minimum variations for all radiation distances and angular ranges were observed for uniform cylindrical electron beam with a radius of 2.0 mm. Anisotropy functions at 0°, F ( r , 0° ), were close to unity and slightly more than unity for non-uniform cylindrical ( R = 1.0 - 2.0 mm) electron beam and uniform cylindrical electron beam with a radius of 2.0 mm. The angles of target anode between 45° and 50° show minimum fluctuations in the anisotropy functions and are close to unity for F ( r , 0° ). The optimal target configurations are a truncated conical-shaped target having an angle between 45° and 50°. It is concluded that tungsten target having the thickness of 1.2 to 1.5 μ m and uniform circular with a radius of 2.0 mm as electron beam produces optimal dosimetric characteristics for electronic brachytherapy X-ray source.